PKM Pembuatan Bahan Ajar Dan Media Pembelajaran Dengan Artificial Intelligence Bagi Guru Di Kota Semarang - Husnul Hadi4; Kartinah Kartinah; Choirul Huda; Aries Tika Damayani (CV. Akira Java Bulu, 2025)
Teachers in the independent curriculum era have more demands than in previous eras. One of them is the mastery of TPACK, which is a framework used by teachers. TPACK contains three components, namely Technology, Pedagogy, and Content where one of the components is the technology used by teachers throughout classroom learning. One of these technologies is Artificial Intelligence (AI). For some teachers, especially elementary school teachers in Semarang City, The results of the workshop showed that 80% of the participants were able to create teaching materials and learning media based on AI, especially utilizing GAMMA and MAGICSCHOOL. It is hoped that this activity can help teachers in learning in the classroom so that the number of teachers who are not technology illiterate will increase and fun learning will be realized